Effects of robotic rehabilitation on fatigue experience, disability, and quality of life in patients with multiple sclerosis (MS): A systematic review and meta-analysis - Abdorreza Naser moghadasi; Mohsen Rastkar; Mehdi Mohammadifar; Aida Mohammadi; Mahsa Ghajarzadeh (Babol University of Medical Sciences, 2024)
Background: Rehabilitation plays an important role in improving symptoms in patients with multiple sclerosis (MS). There are studies evaluating the effects of robotic rehabilitation in patients with MS, but the results varied between the studies. So, we designed this systematic review and meta-analysis to estimate pooled effects of robotic rehabilitation on fatigue, disability, and quality of life in subjects with MS. Methods: We systematically searched PubMed, Scopus, EMBASE, Web of Science, Google Scholar, and also gray literature including references of the included studies, and also conference abstracts on October 1th 2022. Data regarding the total number of participants, first author, publication year, country of origin, mean age, EDSS, and results of fatigue and quality of life were recorded. Results: The first literature search revealed 6878 results, after deleting duplicates, 5019 studies remained. Two researchers, evaluated the titles and abstracts, and finally 77 full texts were assessed. For meta-analysis, we included 11 studies. The pooled Standardized Mean Difference (SMD) of Kurtzke Expanded Disability Status Scale (EDSS) (after-before) estimated as -0.56 (95%CI: -0.89,-0.23). The pooled SMD of Fatigue Severity Scale (FSS) estimated as -0.54(95%CI: -1.06, -0.01) (I2=66.7%, P=0.01). The pooled SMD of physical health subscale of multiple sclerosis quality of life (MSQOL-54) estimated as 0.36(95%CI:-0.23, 0.96) (I2=51.4%, P=0.1). The pooled SMD of mental health subscale of MSQOL54 estimated as 0.48 (95%CI: 0.07, 0.88) (I2=0%, P=0.6). Conclusions: The results of this systematic review and meta-analysis show that robotic rehabilitation has positive effects on fatigue, and disability in patients with MS.